Integration of Alternate Dispute Resolution as a Complement to the Traditional Court System in Pakistan - Shakaib Aleem Arshad; Dr. Hafiz Abdul Rehman Saleem (Research Journal of Psychology, 2025)
This article aims to examine the possibility of alternative dispute resolution (ADR) in Pakistan replacing the country's established legal system. The main objective of the study is to assess the applicability of Alternative Dispute Resolution (ADR) in the Pakistani legal framework, highlighting the advantages and disadvantages of this approach, and compared it to the traditional court system. Like the judicial system of many other countries, Pakistan's judicial system is plagued by serious problems such as backlogs, delays, high costs, and limited access to justice. However, alternative dispute resolution (ADR) methods, including negotiation, mediation, arbitration, and conciliation, have attracted attention because they offer a faster, more affordable, and more flexible way to resolve disputes than traditional dispute settlement system. The study begins with a description of the components and challenges of Pakistan's legal system, and then delves into the concept of Alternative Dispute Resolution (ADR) and its different models. It examines the context of the development and integration of alternative dispute resolution (ADR) into the legal system of Pakistan. The purpose of this evaluation is to identify the strengths and weaknesses of each strategy and to determine whether ADR is an appropriate alternative to resolving the conflict in Pakistan. To provide in-depth knowledge, the study also examines the relevant laws in Pakistan and best practices for the United States, the United Kingdom, and India to improve alternative dispute resolution (ADR) system. The outcomes of this research will contribute to the existing knowledge on ADR in Pakistan, offering practical insights for policymakers and legal professionals. Moreover, it will emphasize ADR's potential to relieve pressure on the court system, lower litigation costs, expedite case resolution, and enhance access to justice for various sectors of society.